Spatial characteristics, similarity in business scope, and expansion network of listed companies in China’s food manufacturing industry - Enkang Li; Yingyi Ma; Bo Hu; Wen Zhong; Ruoyan Zhang (PLoS ONE, 2026)
Using a multi-source dataset of 777 Listed Companies in the Food Manufacturing Industry (LCFMI), this study examines their spatial and relational organization in China. Key findings are: 1) The geographical distribution of LCFMIs closely aligns with China’s macro-economic landscape, with more developed regions hosting a greater concentration and larger scale of firms. 2) While similarity in business scope (SBS) is generally low, significant distance-decay effect is noted, particularly within “0 ~ xx km”; the resulting SBS network demonstrates small-world properties and distinct clustering patterns based on both geography and industrial sub-categories, highlighting the interplay between spatial and cognitive proximity. 3) The inter-city recruitment network, which reflects the spatial expansion of corporate influence, is predominantly shaped by transportation accessibility between cities. This research provides new empirical insights into the geographical organization of manufacturing and the formation of city networks, offering practical implications for regional industrial policy and infrastructure planning.